2015
DOI: 10.1186/s40064-015-1494-5
|View full text |Cite
|
Sign up to set email alerts
|

Materialism, affective states, and life satisfaction: case of Croatia

Abstract: In recent years, a number of studies have used Material Values Scale (MVS) to assess beliefs about importance to own material things. The aims of this study were to validate the MVS scale and to explore the relationships between materialistic values and well-being of Croatian citizens. The study was carried out on a representative sample of N = 1129 Croatian citizens. We used the short 9-item version of the MVS, life satisfaction rating, ratings of two positive (Positive affect) and four negative emotions (Neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
(63 reference statements)
1
12
0
2
Order By: Relevance
“…Conspicuous consumption was measured by adopting the scale used by [14] which was developed by [15]. The level of materialism was measured by using Material Values Scale developed by [16], as used by [17]. This scale consists of 9-item short version form of Material Values Scale of [16].…”
Section: Methodsmentioning
confidence: 99%
“…Conspicuous consumption was measured by adopting the scale used by [14] which was developed by [15]. The level of materialism was measured by using Material Values Scale developed by [16], as used by [17]. This scale consists of 9-item short version form of Material Values Scale of [16].…”
Section: Methodsmentioning
confidence: 99%
“…Based on research by Griffin et al (2004) Lipovčan et al (2015), the dimensions of centrality and success psychometrically do not measure different things, and thus it is recommended by these studies to consider centrality and success as one dimension jointly. Thus, in this study, centrality and success are considered one dimension.…”
Section: Materialistic Value Scale (Mvs)mentioning
confidence: 99%
“…While previous studies consistently show that materialistic value is a multi-faceted construct (Lipovčan, Prizmić-Larsen & Brkljačić, 2015;Richins, 2004), many studies treat materialistic value as a unidimensional construct when analyzing the relation between materialistic value and compulsive buying (Donnelly et al, 2013;Johnson & Attman, 2009;Yurchisin & Johnson, 2004). Those who developed the concept of materialistic value suggested that researchers should measure it with its multiple dimensions (Richins, 2004;Richins & Dawson, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations